Metacognition in schizophrenia: A practical overview of psychometric metacognition assessment tools for researchers and clinicians - Martiadis, Vassilis; Pessina, Enrico; Raffone, Fabiola; Iniziato, Valeria; Martini, Azzurra; Scognamiglio, Pasquale (Frontiers in Psychiatry, 2023)
Metacognition refers to the cognitive ability to control, monitor and modulate cognitive processes thus guiding and orienting behavior: a continuum of mental activities that ranges from more discrete ones, such as the awareness of the accuracy of others’ judgment, to more integrated activities, such as the knowledge of cognitive processes. Metacognition impairment in schizophrenia, which is considered a core feature of the illness, has become a growing research field focusing on a wide range of processes including reasoning, autobiographical memory, memory biases, cognitive beliefs and clinical insight. There is a well-established relationship between metacognition and schizophrenia symptoms severity, as well as between impaired metacognitive functioning and specific symptomatic sub-domains, such as positive symptoms, negative symptoms, or disorganization. The development of specific cognitive-derived psychotherapies for metacognitive deficits in schizophrenia has been ongoing in the last years. Although sharing a metacognitive feature, these treatments focus on different aspects: false or unhelpful beliefs for Metacognitive Therapy; cognitive biases for Metacognitive training; schematic dysfunctional beliefs for CBT for psychoses; metacognitive knowledge and sense of identity for MERIT; interpersonal ideas or events triggering delusional thinking for MIT-P. This article reviews the instruments designed to assess metacognitive domains and functions in individuals with schizophrenia, providing mental health professionals with an overview of the heterogeneous current scenario ranging from self-administered scales to semi-structured interviews, which are supported by a variety of theoretical frameworks. Future directions may address the need for more specific and refined tools, also able to follow-up psychotherapeutic-induced improvements.